Kaji Eksperimental Pengaruh Temperatur Campuran Bahan Bakar Biosolar B20 Dan Crude Palm Oil (CPO) Terhadap Unjuk Kerja Mesin Diesel - Halal Putra Purba; Romy Romy; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The purpose of this research was testing the performance of diesel engines using a mixture of B20 biodieselfuel which commercialized in Indonesia and crude palm oil with a ratio of 95: 5, 90:10 and 85:15 respectively anda pre-heating process for mixtures is carried out. Fuel temperature was varied with 60℃, 75℃ and 90℃ before injection into the combustion chamber and compares the test data with pure B20 biosolar fuel. The performance of a diesel engine showed that by using a fuel mixture there was no significant change in the amount of effective power,torque and BMEP at constant rotation. Specific fuel consumption using a mixture of fuel without preheating process has decreased compared to using pure B20 biodiesel diesel fuel while efficiency increases. SFC value of fuel mixture with preheating process was smaller than the mixture of fuel without preheating but the thermal efficiencyincreased. The ideal temperature of the fuel mixture is 75oC for each mixed variation.Keywords: Diesel engines, biodiesel, performance, pre-heating, crude palm oil